Semantics for Analytic Containment - Correia, Fabrice (My University, 2004)
In 1977, R. B. Angell presented a logic for analytic containment, a notion of “relevant” implication stronger than Anderson and Belnap's entailment. In this paper I provide for the first time the logic of first degree analytic containment, as presented in [2] and [3], with a semantical characterization—leaving higher degree systems for future investigations. The semantical framework I introduce for this purpose involves a special sort of truth-predicates, which apply to pairs of collections of formulas instead of individual formulas, and which behave in some respects like Gentzen's sequents. This semantics captures very general properties of the truth-functional connectives, and for that reason it may be used to model a vast range of logics. I briefly illustrate the point with classical consequence and Anderson and Belnap's “tautological entailments”.
Keywords: analytic containment; relevant implication; semantics